Population ecology - Brown, Harrison Scott 1917-1986; Brown, Harrison Scott 1917-1986; Buchsbaum, Ralph; Buchsbaum, Ralph; Croner, Stanley; Croner, Stanley (Encyclopaedia Britannica Films, 1963)
Muestra las combinaciones de factores que afectan el crecimiento de las poblaciones en la naturaleza.